Stunting Prevention Strategies through the Development of the SiPenTing Application (Sistem Preventif Stunting) in Bondowoso Regency - Molasy, Honest Dody; Zuhri Ernada, Sus Eko; Eriyanti , Linda Dwi; Maidah, Nova El; Rif'ah, Erwin Nur; Hanif, M. Rayhan; Rahayu , Yani Dwi; Infratama Haloho, Hans Christian; Ariyanto, Diki Angger; Diardi, Bellinda Aliefia (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study aims to address the challenge of stunting prevention by developing and implementing the SiPenTing application as a digital technology solution to support local communities. Method: A descriptive qualitative approach was employed, utilizing Focus Group Discussions (FGDs) to gather insights and feedback from stakeholders, including local government officials, village midwives, and mothers participating in integrated service posts. Practical Application: The SiPenTing application facilitates stunting prevention efforts by streamlining communication, providing educational resources, and enhancing monitoring capabilities for both health professionals and community members. Conclusion: The development and implementation of the SiPenTing application in Taman Village, Bondowoso Regency, highlights the transformative potential of digital technology in addressing public health challenges, particularly in preventing stunting. This initiative serves as a model for similar interventions in other regions.